Blood loss from laboratory testing, anemia, and red blood cell transfusion in the intensive care unit: a retrospective study. Issue 2 (28th December 2019) - Jackson Chornenki, Nicholas L.; James, Tyler E.; Barty, Rebecca; Liu, Yang; Rochwerg, Bram; Heddle, Nancy M.; Siegal, Deborah M.
Abstract : BACKGROUND: Anemia is common in critically ill patients and associated with adverse outcomes. Phlebotomy associated with laboratory testing is a potentially modifiable contributor. This study aims to 1) characterize the blood volume taken for laboratory testing, and 2) explore the effect of blood loss on red blood cell (RBC) transfusion and anemia in adult intensive care unit (ICU) patients. METHODS: Using a transfusion research database, we retrospectively reviewed consecutively admitted patients to four medical‐surgical ICUs in Hamilton, Ontario, Canada. The primary outcome was estimated blood loss for laboratory testing during ICU admission. Secondary outcomes were hemoglobin (Hb) of 90 g/L or less and RBC transfusion. RESULTS: Among the 7273 patients included, the median blood volume per patient taken for laboratory testing during their ICU stay was 213 mL (interquartile range [IQR], 133‐382 mL). On ICU admission, median Hb was 97 g/L (IQR, 82‐116 g/L). An Hb of 90 g/L or less occurred in 67.0% of patients during their ICU stay. Median Hb on ICU discharge adjusted for RBC transfusion was 84 g/L (IQR, 58‐105 g/L). RBC transfusion was administered to 47.5% of patients, who received a median of 3 units (IQR, 2‐7 units). Cumulative blood loss due to laboratory testing from Day 2 to Day 7 of ICU admission was independently associated with RBC transfusion (hazard ratio, 2.28 for each 150‐mL increment; 95% confidence interval, 2.02–2.59). CONCLUSIONS: Blood loss for laboratory testing is substantial in ICU patients and significantly associated with RBC transfusion. Strategies to reduce blood loss from laboratory testing represents an area for further investigation.